Production process of random copolymerization soft fiber high-end hygienic material special material

Through the production process of random copolymerized soft fiber high-end Haimei special materials, the problems of thick wire drawing, many burrs and poor soft performance of gas-phase homopolymerized polypropylene materials are solved, and more detailed spinning and better feel are achieved, soft and soft Increased by more than 15%.

CN119192734AActive Publication Date: 2024-12-27PETROCHINA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310745260.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2024-12-27
Estimated Expiration
2043-06-25

AI Technical Summary

Technical Problem

The existing gas phase method is thicker in the polypropylene material, with many burrs in the product, and poor softness performance, making it difficult to meet the softness and feel requirements of high-end clothing materials such as baby diapers, elderly diapers and surgical gowns.

Method used

Using the production process of random copolymer soft fiber high-end Haicai special materials, through prepolymerization, random copolymerization and peroxide degradation reactions, polypropylene powder with narrower molecular weight distribution and higher melt flow rate is generated, combined with specific Catalysts and additives to regulate the melt index and flexibility of the product.

Benefits of technology

It improves the softness of non-woven products, the diameter of the wire is thinner and more uniform, solves the burr problem, the product feels better, and the softness is more than 15% higher than that of traditional homogeneous products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004298773090000071
    Figure BDA0004298773090000071
  • Figure BDA0004298773090000072
    Figure BDA0004298773090000072
Patent Text Reader

Abstract

The invention provides a production process of a special material for a random copolymerization soft fiber high-end sanitary material, and mainly solves the problems of thicker drawn wires, more burrs and poor softness of a homo-polypropylene material prepared by the existing gas phase method. The method is characterized by comprising the following steps: S1, prepolymerization reaction: prepolymerizing a catalyst and propylene to generate a prepolymerization product; s2, random copolymerization reaction: under the action of a catalyst, carrying out random copolymerization reaction on the generated prepolymerization product, gas-phase propylene and a small amount of ethylene to obtain polymer basic powder under polymerization process conditions; and S3, peroxide degradation reaction: blending the obtained polymer basic powder with an additive, degrading with an oxide degradation agent, and carrying out melt extrusion granulation to obtain a target product. According to the production process of the special material for the random copolymerization soft fiber high-end sanitary material, a special material non-woven fabric product is good in softness, the diameter of filaments is thinner and more uniform, and the hand feeling of the product is more excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of olefin polymerization, and in particular to a production process of a random copolymer soft fiber special material for high-end sanitary materials. Background Art

[0002] The main methods for producing high-flow non-woven fabric special PP by gas phase method in industry are hydrogen adjustment method and degradation method (also called controlled rheology method). The hydrogen adjustment method is to add a certain amount of hydrogen during the polymerization of propylene to adjust the relative molecular weight and distribution of polypropylene to produce polypropylene with a higher melt flow rate; the degradation method is to first polymerize propylene into a powder with a lower melt flow rate, then add liquid or solid peroxide for degradation, and extrude and granulate to obtain a polypropylene product with a higher melt flow rate and a narrow relative molecular weight distribution. After the degradation of the polypropylene base powder, the distribution of the polypropylene molecular weight will become narrower, and the spinnability of the fiber material will be enhanced. Therefore, when the gas phase method is used to produce fiber-grade high melt flow rate polypropylene special materials, the degradation method is used, which is achieved by degradation of homopolymer polypropylene by peroxide. When it is processed into non-woven fabrics, the spun silk is coarser and the product is not soft enough. Softeners and other auxiliary materials need to be added to improve the processing performance and use performance.

[0003] At present, the raw materials of domestic high-end non-woven fabrics (baby diapers, elderly diapers, surgical gowns and operating room supplies) are polypropylene homopolymer products, the produced wires are relatively coarse, the wire drawing diameter can only reach about 2 deniers, the softness of the products does not meet the requirements, and the sanitary materials produced have burrs, irritating the skin and affecting the feel. The present invention solves the problems of coarse wire drawing of homopolymerized polypropylene materials, many burrs in the products, and poor softness. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the problems of coarse wire drawing, many burrs and poor softness of the existing gas phase homopolymerized polypropylene materials in the background technology, and to provide a production process for a random copolymerized soft fiber high-end sanitary material special material. The production process for the random copolymerized soft fiber high-end sanitary material special material has good softness, which is more than 15% higher than that of the traditional homopolymerized products; at the same time, the diameter of the wire is thinner and more uniform, which solves the problem of burrs and makes the product feel better.

[0005] The present invention solves the problem by the following technical solution: The production process of the random copolymer soft fiber high-end sanitary material comprises the following steps:

[0006] Step 1: Prepolymerization

[0007] Prepolymerizing the catalyst and propylene to generate a prepolymer product under prepolymerization reaction conditions;

[0008] Step 2: Random Copolymerization

[0009] Under the action of a catalyst, the generated prepolymer product is subjected to random copolymerization reaction with gas-phase propylene and ethylene, and under polymerization process conditions, a polymer base powder is obtained;

[0010] Step 3: Peroxide degradation reaction

[0011] The obtained polymer base powder is then blended with additives, degraded by an oxide degradation agent, the melt index of the product is adjusted, and the target product is obtained by melt extrusion granulation.

[0012] Furthermore, the catalyst in step 1 and step 2 is composed of a main catalyst, a co-catalyst and an electron donor; the main catalyst is ZN118 and / or CS2, the co-catalyst is triethylaluminum; and the electron donor is DonorC.

[0013] Furthermore, in step 1 and step 2, the ratio of the main catalyst ZN118 to CS2 is 1:1; the ratio of the co-catalyst to the catalyst is 3-5:1, and the ratio of the co-catalyst to the electron donor is 2-10:1.

[0014] Furthermore, the catalyst for the prepolymerization reaction needs to be mixed with the oil under nitrogen protection conditions, pre-contacted at 15°C, and then enter the prepolymerization reactor to undergo a prepolymerization reaction with the propylene entering through the online mixer; the oil component is a mixture of white oil and vaseline in a volume ratio of 2:1.

[0015] Furthermore, the prepolymerization reaction process conditions are: the prepolymerization is carried out in a bulk propylene liquid phase environment, at a temperature of 25°C-30°C and a pressure of 2.8Mpa-3.2Mpa in a small loop tube, and the residence time is 10-20 minutes.

[0016] Furthermore, the polymerization process conditions of the random copolymerization reaction in step 2 are: temperature 70°C-75°C, pressure 2.7MPa-3.0MPa, residence time 1 hour and 20 minutes; the ratio of co-catalyst to catalyst is 3-5:1, and the ratio of co-catalyst to electron donor is 2-10:1 (TEAL / CAT is 3-5, TEAL / Donor is 2-10); the polymerized ethylene is controlled at 2.0%-3.0% (mass percentage), and hydrogen is added to the multi-zone circulation reactor to adjust the molecular weight to ensure that the melt index (abbreviated as melt index, also known as melt mass flow rate MFR) of the random copolymer polypropylene powder generated in the reactor is 7.0-10.0g / 10min.

[0017] Furthermore, the additive antioxidant system in step 3 is a composite antioxidant (B215 and calcium stearate composite antioxidant), and the added amount is 1000ppm-2000ppm; the added degradation agent is peroxide 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane, also known as TRIGONOX101.

[0018] Furthermore, the additives in step 3 are single doses, and the single doses are IRGANOX 1010 additive, IRGAFOS 168 additive and calcium stearate, which are compounded in a mass ratio of 1:2:2.

[0019] Furthermore, the target product pellets produced in step 3 have a melt index of 35.0-40.0 g / 10 min.

[0020] Furthermore, the target product generated in step 3 is used to prepare non-woven high-end sanitary materials, and the softness of the special non-woven fabric products is more than 15% higher than that of traditional homopolymer products.

[0021] The production process reaction mechanism of the random copolymer soft fiber high-end sanitary material special material of the present invention is as follows:

[0022] The random copolymerized soft fiber high-end sanitary material special material of the present invention is prepared by random copolymerization of gas phase propylene and gas phase ethylene to embed ethylene in the long chain structure of polypropylene, and then blended with additives, degraded by oxides, and melt extruded and granulated to obtain the target product. The catalyst system (CAT) is a Ziegler-Natta type catalyst and its carrier, configured with a co-catalyst triethylaluminum (TEAL-Triethylaluminum). The electron donor Donor C (cyclohexylmethyldimethoxysilane) is a liquid silane, which is used as a co-catalyst to adjust the isotacticity of the high-efficiency catalyst. Too much addition will lead to reduced catalyst activity, and only polymerization with a high-efficiency catalyst will produce a product with a high content of random polymers. Random polymers are different from isotactic polymers. Random polymers are very viscous. A small amount of random substances in the finished product is beneficial to prevent embrittlement and improve impact strength. The content of random substances in the final product is controlled by the amount of electron donor added.

[0023] Compared with the above background technology, the present invention has the following beneficial effects:

[0024] The production process of the random copolymerized soft fiber high-end sanitary material special material of the present invention adopts the random copolymerized soft fiber high-end sanitary material special material, which is prepared by random copolymerization of gas phase propylene and gas phase ethylene to embed ethylene in the long chain structure of polypropylene, and then blended with additives, degraded by oxides, and melt extruded and granulated to obtain the target product. The polymerized ethylene is controlled at 2.0%-3.0%. The non-woven fabric products of the special material have good softness, which is more than 15% higher than the softness of traditional homopolymer products, and has irreplaceable advantages in the field of silky soft sanitary materials. At the same time, the diameter of the silk is thinner and more uniform, which solves the problem of burrs and makes the product feel better. Specific implementation method:

[0025] The present invention will be further described below in conjunction with specific embodiments:

[0026] The production process of the random copolymer soft fiber high-end sanitary material comprises the following steps:

[0027] Step 1: Prepolymerization

[0028] The catalyst and propylene are prepolymerized at a temperature of 25°C-30°C and a pressure of 2.8Mpa-3.2Mpa for a residence time of 10-20 minutes to generate a prepolymerized product.

[0029] The catalyst used is composed of a main catalyst, a co-catalyst and an electron donor; the main catalyst is ZN118 and / or CS2, the co-catalyst is triethylaluminum; the electron donor is DonorC (cyclohexylmethyldimethoxysilane), which is a liquid silane and acts to adjust the isotacticity of the high-efficiency catalyst.

[0030] The ratio of the main catalyst (CAT) ZN118 to CS2 is 1:1; the ratio of the co-catalyst to the main catalyst is 3-5:1, and the ratio of the co-catalyst to the electron donor is 2-10:1.

[0031] Step 2: Random Copolymerization

[0032] Under the action of the catalyst, the generated prepolymer product is subjected to random copolymerization reaction with gas-phase propylene and a small amount of ethylene. The polymerization process conditions are as follows: temperature 70°C-75°C, pressure 2.7MPa-3.0MPa, residence time 1 hour and 20 minutes, TEAL / CAT 3-5, TEAL / Donor 2-10, polymerized ethylene is controlled at 2.0%-3.0% (mass percentage), hydrogen is added to the multi-zone circulation reactor to adjust the molecular weight, and the melt index (abbreviated as melt index, also known as melt mass flow rate MFR) of the random copolymer polypropylene generated in the reactor is ensured to be 7.0-10.0g / 10min, so as to obtain a polymer base powder.

[0033] Step 3: Peroxide degradation reaction

[0034] The obtained polymer base powder is then blended with additives, subjected to oxide degradation, and melt-extruded and granulated to obtain the target product.

[0035] The additive is a compound antioxidant of B215 and calcium stearate, or a single dose of IRGANOX 1010 additive, IRGAFOS 168 additive and calcium stearate compounded in a mass ratio of 1:2:2, and the added amount is 1000ppm-2000ppm.

[0036] The peroxide degradation agent used in the oxide degradation process is 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane, also known as TRIGONOX 101, which is used to degrade the polymer chains produced by polymerization. The addition amount is 350ppm-550ppm, and the product melt index is regulated to be 35.0-40.0g / 10min. The main process of the granulation part of the present invention is adjusted to a barrel temperature between 240℃-260℃ and a melt temperature of 200℃-230℃.

[0037] Example 1

[0038] The propylene polymerization reaction is carried out on a polypropylene unit, using the polymerization process control technology of the Spherizone process and a multi-zone circulation reactor. The main equipment includes a prepolymerization reactor, a multi-zone circulation reactor and an extrusion granulator.

[0039] (1) First step: prepolymerization

[0040] Three catalysts are required: main catalyst (CAT) ZN118+CS2 (ratio is 1:1), co-catalyst TEAL (triethylaluminum), and electron donor Donor C.

[0041] The catalyst needs to be configured under nitrogen protection conditions, mixed with oils and fats (white oil and vaseline, volume ratio 2:1), and then pre-contacted at 15°C before entering the prepolymerization reactor to undergo prepolymerization reaction with propylene entering through an online mixer to generate a prepolymerization product.

[0042] The prepolymerization is carried out in a bulk propylene liquid phase environment at a temperature of 25°C-30°C and a pressure of 2.8Mpa-3.2Mpa in a small loop tube, with a residence time of 10-20 minutes.

[0043] (2) Step 2: Random Copolymerization

[0044] The prepolymerized powder is subjected to random copolymerization reaction with gas phase propylene and a small amount of ethylene in a multi-zone circulation reactor to obtain a polymer powder.

[0045] The polymerization process conditions are as follows: temperature 70℃-75℃, pressure 2.7MPa-3.0MPa, residence time 1 hour 20 minutes, TEAL / CAT 3-5:1, TEAL / Donor 2-10:1, and the polymerization ethylene is controlled at 2.0%-3.0% (mass percentage). Hydrogen is added to the multi-zone circulation reactor to adjust the molecular weight, ensuring that the melt index (abbreviated as melt index, also known as melt mass flow rate MFR) of the random copolymer polypropylene generated in the reactor is 7.0-10.0g / 10min, and polymer powder is obtained.

[0046] (3) Step 3: Peroxide degradation reaction

[0047] The activity of the unreacted catalyst in the polymer powder is removed by hot nitrogen and heated to dry to obtain the treated polymer base powder. The additive antioxidant system is a compound antioxidant of B215 and calcium stearate, with an addition amount of 1000ppm-2000ppm; the added degradation agent is peroxide TRIGONOX 101, with an addition amount of 350ppm-550ppm, and the product melt index is regulated to 35.0-40.0g / 10min. Granulation is carried out using a twin-screw extruder, in which the amount of degradation agent is adjusted according to the requirements of the melt index of the polymer powder and the melt index of the final pellet product. The process parameters and the physical properties of the obtained polymer products are shown in Tables 1 and 2.

[0048] Example 2

[0049] Example 2 Prepolymerization, random copolymerization reaction conditions, auxiliary agent formulation and addition amount are the same as those in Example 1. The difference from Example 1 is that the catalyst used is imported ZN118. The process parameters and the physical properties of the obtained polymer product are shown in Tables 1 and 2.

[0050] Example 3

[0051] The catalyst, prepolymerization and polymerization process conditions used in Example 3 are the same as those in Example 1. The difference from Example 1 is the type and amount of additives. The single agents added to the powder obtained by polymerization are IRGANOX 1010 additive, IRGAFOS 168 additive and calcium stearate, respectively, in a ratio of 1:2:2, and the degradation agent is TRIGONOX 101 (Nouryon Functional Chemicals BV, the Netherlands).

[0052] Comparative Example 1

[0053] The method of producing high-fluidity non-woven fabric special PP by the existing gas phase method, the catalyst and prepolymerization used are the same as those in Example 2, except that the second step reaction of Comparative Example 1 is a homopolymerization reaction without adding ethylene, and hydrogen is added to adjust the molecular weight to ensure that the homopolymerized polypropylene melt index MFR generated in the reactor is 2.4-3.6g / 10min, and a polymer base powder is obtained. Since the base powder has a small melt index, the amount of degradation agent added to obtain the polypropylene pellets with the required melt index is correspondingly larger. The process parameters and the physical property data of the obtained polymer product are shown in Tables 1 and 2.

[0054] The polymer data in the above Examples 1-3 and Comparative Example 1 were obtained by the following test methods:

[0055] ① Melt mass flow rate MFR: measured according to the method described in GB / T3682-2000; measured using CEAST's 7026 melt indexer at 230°C and 2.16kg load;

[0056] ②Tensile strength: measured according to the method described in GB / T1040-2006, using ZWICK's BT1-FR005TN.A50 universal material testing machine;

[0057] ③ Flexural modulus: measured according to the method described in GB / T9341-2008; using ZWICK's BT1-FR005TN.A50 universal material testing machine;

[0058] ④ Impact strength: measured according to the method described in GB / T1843-2008, using BPI-5.5STAC from ZWICK;

[0059] ⑤ Oxidation induction period: Determined according to the method described in GB / T2951.1-1994, using the Q20 DSC instrument of Waters China Co., Ltd., 10±0.5 mg of the sample was heated to 200°C at a rate of 20°C / min under nitrogen protection, kept constant for 5 minutes, then the nitrogen was stopped and oxygen was passed at a flow rate of 50 mL / min;

[0060] ⑥ Melting point / crystallization temperature / : Determined according to the method described in GB / T 19466-2004, using Q20 DSC of Waters China Co., Ltd., under the protection of N2 with a flow rate of 50 ml / min, 5±0.5 mg of sample was first heated from room temperature to 200°C at a heating rate of 10°C / min, and kept at this temperature for 5 min to eliminate the thermal history, then cooled to 40°C at a cooling rate of 10°C / min, kept at this temperature for 5 min, and then heated to 200°C at 10°C / min again;

[0061] ⑦Ash content: measured according to the method described in GB / T9345.1;

[0062] ⑧ Vinyl: determined according to the method described in SN / T3298-2012;

[0063] ⑨ Yellow index: measured according to the method described in HG / T 3862-2006, using a yellow index meter from HUNTERLAB.

[0064] Table 1. Process parameters of the examples

[0065]

[0066] Table 2. Physical property analysis data results of polymers in the examples

[0067]

[0068] As can be seen from Table 2, the random copolymer polypropylene product prepared by the production process of the random copolymer soft fiber high-end sanitary material special material of the present invention is compared with various indicators of the existing products. Due to the addition of a small amount of ethylene and the optimization of ethylene distribution, the bending modulus and melting point of the polypropylene product are reduced, and the good spinning performance of the product and the softness of the non-woven fabric product are increased.

[0069] The non-woven high-end sanitary products (baby diapers, elderly diapers, surgical gowns and operating room supplies) prepared by the special materials of the process of the present invention have good softness, which is more than 15% higher than the softness of traditional homopolymer products, and has irreplaceable advantages in the field of silky soft sanitary products. At the same time, the diameter of the silk is thinner and more uniform, which solves the problem of burrs and makes the product feel better.

[0070] The raw materials and components used in the above examples are all commercially available.

[0071] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Therefore, the content of the present invention is not limited to the examples listed, and any equivalent changes taken by ordinary technicians in the field of the present invention by reading the specification of the present invention to the technical solution of the present invention are all covered by the claims of the present invention.

Claims

1. A production process for a random copolymer soft fiber high-end sanitary material, characterized by: The following steps are involved: Step 1: Prepolymerization Prepolymerizing the catalyst and propylene to generate a prepolymer product under prepolymerization reaction conditions; Step 2: Random Copolymerization Under the action of a catalyst, the generated prepolymer product is subjected to random copolymerization reaction with gas-phase propylene and ethylene, and under polymerization process conditions, a polymer base powder is obtained; Step 3: Peroxide degradation reaction The obtained polymer base powder is then blended with additives, degraded by an oxide degradation agent, the melt index of the product is adjusted, and the target product is obtained by melt extrusion granulation.

2. The production process of the random copolymer soft fiber high-end sanitary material according to claim 1 is characterized by: The catalyst in step 1 and step 2 is composed of a main catalyst, a co-catalyst and an electron donor; the main catalyst is ZN118 and / or CS2, the co-catalyst is triethylaluminum; and the electron donor is DonorC.

3. The production process of the random copolymer soft fiber high-end sanitary material according to claim 2 is characterized by: In the steps 1 and 2, the ratio of the main catalyst ZN118 to CS2 is 1:1; the ratio of the co-catalyst to the main catalyst is 3-5:1, and the ratio of the co-catalyst to the electron donor is 2-10:

1.

4. The production process of the random copolymer soft fiber high-end sanitary material according to claim 1 is characterized by: The catalyst for the prepolymerization reaction needs to be mixed with oil and fat under nitrogen protection conditions, and then enter the prepolymerization reactor after pre-contact at 15°C to undergo prepolymerization reaction with propylene entering through an online mixer; the oil component is a mixture of white oil and vaseline in a volume ratio of 2:

1.

5. The production process of the random copolymer soft fiber high-end sanitary material according to claim 1 is characterized by: The prepolymerization reaction process conditions are as follows: the prepolymerization is carried out in a bulk propylene liquid phase environment, at a temperature of 25°C-30°C and a pressure of 2.8Mpa-3.2Mpa in a small loop tube, with a residence time of 10-20 minutes.

6. The production process of the random copolymer soft fiber high-end sanitary material according to claim 1 is characterized by: The polymerization process conditions of the random copolymerization reaction in step 2 are: temperature 70°C-75°C, pressure 2.7MPa-3.0MPa, residence time 1 hour and 20 minutes; the ratio of co-catalyst to main catalyst is 3-5:1, and the ratio of co-catalyst to electron donor is 2-10:1; the mass percentage of polymerized ethylene is controlled at 2.0%-3.0%, and hydrogen is added to the multi-zone circulation reactor to adjust the molecular weight to ensure that the melt index of the random copolymer polypropylene powder generated in the reactor is 7.0-10.0g / 10min.

7. The production process of the random copolymer soft fiber high-end sanitary material according to claim 1 is characterized by: The additive antioxidant system in step 3 is a composite antioxidant, which is an antioxidant compounded with B215 and calcium stearate, and the added amount is 1000ppm-2000ppm; the added degradation agent is peroxide 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane, also known as TRIGONOX 101.

8. The production process of the random copolymer soft fiber high-end sanitary material according to claim 1 is characterized by: The additives in step 3 are single doses, and the single doses are IRGANOX 1010, IRGAFOS 168 and calcium stearate, which are compounded in a mass ratio of 1:2:

2.

9. The production process of the random copolymer soft fiber high-end sanitary material according to claim 1, characterized in that: The target product pellets generated in step 3 have a melt index of 35.0-40.0 g / 10 min.

10. The production process of the random copolymer soft fiber high-end sanitary material according to claim 1 or 9, characterized in that: The target product generated in step 3 is used to prepare cloth-free high-end sanitary materials.

Citation Information

Patent Citations

  • Random propylene copolymer applied to ultra-soft nonwoven fabric and preparation method of random propylene copolymer

    CN106554569A

  • Scratch-resistant high-impact random co-polypropylene and preparation method thereof

    CN109593276A

  • Polypropylene material for non-woven fabric and preparation method thereof

    CN112266535A

  • Polypropylene random copolymer base material, preparation method thereof and polypropylene fiber material containing base material

    CN112341557A

  • Preparation method of polypropylene material

    CN114426740A